A Sector Wise Influence of Equity Ownership Holding on the Corporate Debt Policy- An Empirical Analysis - Shunmughan, R.; E.P., Sengottuvel (Ushus Journal of Business Management, 2010)
This paper aims to analyse the effect of equity ownership holding pattern on the corporate debt policy under a sector wise classification. The study uses a sample of thirty six firms in the construction of BSE- 200 index during the period 1999-2009. The study has used Regression analysis and Descriptive statistics to quantify the argument. This paper finds a significant relationship between debt policy and public holding pattern in all the sectors. Promoters holding show insignificant relation for the Transport and Power sector.